USING ARTIFICIAL INTELLIGENCE TOOLS AS A METHOD TO ENSURE CONSUMERS' ACCESS TO JUSTICE - Amantay, Абдолла; Nurmagambetov, Аманжол Магзумович; Akhpanov , Арыстан Нөкешұлы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
The aim of this study is to provide a scientific rationale for the use of artificial intelligence (AI) tools to improve access to justice for consumers in need of legal assistance. The relevance of the topic lies in the fact that many consumers struggle to protect their rights effectively due to a lack of legal information and the complexity of court procedures. This article explores the potential of modern AI technologies such as chatbots, online legal advisors, and algorithmic decision-making systems. The analysis identifies major challenges: low legal literacy, high litigation costs, and geographic barriers. Advantages of AI include increased accessibility, faster legal assistance, reduced costs, and minimized reliance on human intervention. However, risks such as algorithmic errors, data privacy concerns, and overreliance on automated systems are also discussed. The paper examines pilot projects in Kazakhstan (e.g., the Ministry of Justice’s legal chatbot and the virtual assistant "Aiteke" in the IPrav mobile app) alongside international best practices. The methodology includes comparative legal analysis, expert interviews, and statistical data review. The study concludes that AI integration into the legal services system significantly enhances consumers' access to justice, provided that technological infrastructure, legal regulations, and human oversight are adequately ensured.